2013
DOI: 10.1016/j.poly.2012.07.098
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and structural properties of InIII–OH complexes

Abstract: The use of the tripodal ligands tris[(N'-tert-butylureaylato)-N-ethyl]aminato ([H3buea]3−) and the sulfonamide-based N,N',N"-[2,2',2"-nitrilotris(ethane-2,1-diyl)]tris(2,4,6-trimethylbenzene-sulfonamidato) ([MST]3−) has led to the synthesis of two structurally distinct In(III)–OH complexes. The first example of a five-coordinate indium(III) complex with a terminal hydroxide ligand, K[InIIIH3buea(OH)], was prepared by addition of In(OAc)3 and water to a deprotonated solution of H6buea. X-ray diffraction analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Our earlier work showed that incorporation of urea groups into tripodal ligands provides excellent H-bond donors to metal-oxido/hydroxido units, whereas sulfonamide groups serve as H-bond acceptors. For instance, the symmetric urea-based tripod [H 3 buea] 3– forms stable monomeric Moxido complexes (M = Mn, Fe) and M′–OH complexes (M′ = Mn, Fe, Co, Zn, In). ,,, The accessibility to these high valent complexes was attributed to the highly anionic ligand field that was provided by the deprotonated nitrogen donors from [H 3 buea] 3– and the oxido/hydroxido ligands. In contrast to [H 3 buea] 3– , the symmetrical sulfonamide-based ligand ( N,N ′ ,N ″-(nitrilo­tris­(ethane-2,1-diyl))­tris­(2,4,6-trimethyl­benzene-sulfonamido)) [MST] 3– (Figure ) utilizes the sulfonamido oxygen atoms as H-bond acceptors.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier work showed that incorporation of urea groups into tripodal ligands provides excellent H-bond donors to metal-oxido/hydroxido units, whereas sulfonamide groups serve as H-bond acceptors. For instance, the symmetric urea-based tripod [H 3 buea] 3– forms stable monomeric Moxido complexes (M = Mn, Fe) and M′–OH complexes (M′ = Mn, Fe, Co, Zn, In). ,,, The accessibility to these high valent complexes was attributed to the highly anionic ligand field that was provided by the deprotonated nitrogen donors from [H 3 buea] 3– and the oxido/hydroxido ligands. In contrast to [H 3 buea] 3– , the symmetrical sulfonamide-based ligand ( N,N ′ ,N ″-(nitrilo­tris­(ethane-2,1-diyl))­tris­(2,4,6-trimethyl­benzene-sulfonamido)) [MST] 3– (Figure ) utilizes the sulfonamido oxygen atoms as H-bond acceptors.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the tripodal ligand N , N ′, N ″-[2,2′,2″-nitrilotris­(ethane-2,1-diyl)]­tris­(2,4,6-trimethylbenzenesulfonamido) ([MST] 3– ) can be used to prepare monometallic complexes with various metal ions. These monomeric species can be oxidized with O 2 in the presence of a second metal ion (M II ) and a capping ligand (L) to form bimetallic species of the formulation [(L)­M II -(μ-OH)-M III MST] + (Figure ). The two metal centers have different coordination environments and are bridged by a hydroxido ligand formed via the activation of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…1). [15][16][17][18][19] Because of these structural features, we reasoned that complexes of [MST] 3À should be ideally suited to stabilize species with a terminal ammonia ligand.…”
mentioning
confidence: 99%